MRI compatibility testing of commercial high intensity focused ultrasound transducers - Evripidou, Nikolas; Antoniou, Anastasia; Georgiou, Leonidas; Ioannides, Cleanthis; Spanoudes, Kyriakos; Damianou, Christakis A. (My University, 2024)
The study aimed to compare the performance of eight commercially available single-element High Intensity Focused Ultrasound (HIFU) transducers in terms of Magnetic Resonance Imaging (MRI) compatibility.
Keywords: Artifacts; Commercial; Compatibility; HIFU; MRI; Transducer